ELECTROCHEMICAL PERFORMANCES OF NITROGEN-DOPED CARBON/MNO2 COMPOSITE SUPERCAPACITOR ELECTRODE IN KI-ADDED NA2SO4 ELECTROLYTE - Sutarsis, Sutarsis; Abyan, Demas Muhammad; Kussuma, Fahrul Ardian Firmanda; Pradesar, Yusuf; Purniawan, Agung (Department of Mechanical Engineering Education, 2024)
In this study, Nitrogen-doped Activated Carbons (NAC) with different Nitrogen concentrations (NAC1, NAC2, NAC3) and Manganese Dioxide (MnO2) were composited to make the hybrid active material for supercapacitor electrodes to improve the energy density of NAC by adding the pseudo-redox capacitive properties of NAC/MnO2 composite electrode. NAC active material was made from the pyrolyzing biomass carbon and Polyaniline mixture at 800 °C in a nitrogen atmosphere for 2 hours. NAC/MnO2 hybrid material was synthesized by heating NAC: MnO2 with a ratio of 5:1 at 400 °C for 2 hours. Peaks analysis of X-ray diffraction of NAC/MnO2 powder shows that the MnO2 phase was formed as a composite with NAC. The electrochemical performance of the NAC3/MnO2 electrode exhibited the highest capacitance of 168 Fg-1 at a scan rate of 5 mVs-1 in Potassium Iodide (KI)-added Na2SO4 electrolyte. According to the Cycle Voltammetry (CV) measurement, the NAC3/MNO2 composite electrode shows hybrid capacitive behavior consisting of pseudo-redox and double-layer electrostatic energy storage mechanisms in KI-added Na2SO4 electrolyte. NAC3/MnO2 composite electrode demonstrates a high energy density of 22 Whkg-1 at 5 mVs-1.